Supply Chain Strategy for Measuring Risk through Capital Allocation: An Application of Incremental and Activity Based Methods - Sukono Sukono; Stanley Pandu Dewanto; Dwi Susanti; Candra Budi Wijaya; Nurfadhlina Abdul Halim; Jumadil Saputra (International Journal of Supply Chain Management, 2020)
the insurance company needs a good strategy for ensuring its existence and ability to survive in the insurance world competition with reducing the chance of loss risk. Thus, this paper is written to investigate the capital allocation for measuring risk via a mathematical approach namely Value-at-Risk (VaR) so that insurance companies can find out the magnitude of the worst risks that may occur. The amount of capital allocation analysed using Incremental and Activity-Based Methods. Also, this study uses the simulation data of random numbers obtained from the calculation of premium and claims for insurance programs. The results of the analysis showed that a positive value for the diversification process. It indicates that the insurance company has met its obligations. The total risk of all portfolio returns is IDR19,013,620,433.00. Using the capital allocation analysis, this study found that the Portfolio 1 as much as IDR4,938,935,765.00, Portfolio 2 is IDR4,787,472,037.00, and Portfolio 3 as big as IDR5,544,572,898.00.